The Hobbit, Or, There and Back Again - Tolkien, J. R. R. (London Unwin Paperbacks, 1981)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.